EMERGING IN THE PROCESS OF DIGITALIZATION OF HIGHER EDUCATION - Turganbayeva, А.Р.; Шахан, А.Е. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article provides an overview of the risks that arise in the process of digitalization of higher education. Despite all the achievements and positive aspects of the process of digitalization of society as a whole and, in particular, in higher education, a large number of different risks arise. These include the emergence of psychological problems, pedagogical-the possible loss of pedagogical ideas that do not obey the processes of digitalization, methodological – when changing various platforms and teaching methods, technical and technological – there are problems of copyright protection and information security, difficulties in mastering technology, especially for older teachers, which can lead to discrimination against teachers and other undesirable changes in the economy and society, including in the higher education system. The article shows the possibilities of digital technologies, their impact on the emergence of risks in the economy and disappointing changes in the education system.